MODEL FOR ASYMPTOTIC D-STATE PARAMETERS OF LIGHT-NUCLEI - APPLICATION TO HE-4 - Adhikari, S. K.; Frederico, T.; Goldman, I. D.; Sharma, S. S. (American Physical Soc, 1994)
A simple method for calculating the asymptotic D-state observables for light nuclei is suggested. The method exploits the dominant clusters of the light nuclei. The method is applied to calculate the He-4 asymptotic D to S normalization ratio rho(alpha) and the closely related D-state parameter D2alpha. The study predicts a correlation between D2alpha and B(alpha), and between rho(alpha) and B(alpha), where B(alpha) is the binding energy of He-4. The present study yields rho(alpha) congruent-to -0.14 and D2alpha congruent-to -0.12 fm2 consistent with the correct experimental eta(d) and the binding energies of the deuteron, triton, and the alpha particle, where eta(d) is the deuteron D-state to S-state normalization ratio.